The historical development of the results of the Iraqi Olympic team participating in the Olympics since 1960 AD until 2004 AD - Ali Mohammed Khalaf, (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research appears in knowing the development taking place in the results of the Iraqi Olympic team participating in the Olympics since 1960 AD in Rome and until the year 2004 AD in Athens as a step to find out the reasons for the development of these results in some tournaments versus fluctuation in other tournaments.This is what prompted the researcher through this research to reach the results achieved by the Iraqi Olympic team in its participation in the Olympic Games, to be a contribution to the service of the sons of our beloved country. The researcher touched on the relevant theoretical aspects, his profile on the Olympic Games, past and present, and the establishment of the Iraqi National Olympic Committee.As for the research methodology, the researcher used the historical curriculum or the so-called documentary approach, benefiting from showing Iraq’s external participation in the Olympics exclusively to suit the objectives of the study (as the historical curriculum is a description and recording of the facts and past events, analysis and interpretation of them to reach facts intended to develop future plans. The results of the Iraqi Olympic football team participating in the Olympic Games and during (11) tournaments from 1960 to 2004, except for the Barcelona tournament in (1992), he apologized for participating due to the Gulf War. As for the results of the research, they have been classified through Table (1), which shows the results of the Iraqi Olympic team participating in the Olympic Games since 1960 AD until 2004 AD. Through the results, the researcher reached the most important conclusions, including: 1. The number of Iraq’s participation in the Olympic Games since 1960 AD in the year 2004 AD was Athens (11) and not participating in Barcelona in 1992 due to the Gulf events 2. The number of goals scored by the Iraqi Olympic team in the Olympic Games in which they participated since 1960 AD until 2004 AD reached 129 goals through (82) matches played in the qualifiers. 3. The Olympic team faced in Athens in 2004 AD sports teams from various continents (Costa Rica) from (Central America), Portugal (continent of Europe), Morocco (continent of Africa), Uruguay (Latin America) and Italy (continent of Europe)